An analytical look at 20th century trumpet music, including works by JosephTurrin, Vincent Persichetti, Alexander Goedicke, and Eric Ewazen - Johnson, James (Kansas State University, 2013)
This report is an in-depth analysis of selected music written for the trumpet during the 20th century, including composer biographies and theoretical analysis for each piece. The pieces included in this report are Joseph Turrin’s Caprice, Vincent Persichetti’s The Hollow Men, Alexander Goedicke’s Concert Etude, and Eric Ewazen’s Sonata for Trumpet and Piano as well as his Concert Fanfare for Six Trumpets.
Keywords: Trumpet; Turrin; Ewazen; Persichetti; Goedicke; Music; Music (0413)